Effects of enhanced solution treatment on microstructure and mechanical properties of Al–Cu–Li–Sc alloy. Issue 10 (3rd July 2018) - Yang, Ruibin; Zhi, Qian; Wang, Feizhou; Zhang, Yunjie; Liu, Zhongxia; Wang, Jiefang; Tan, Xinrong; Chen, Yadong; Cao, Yanjie
ABSTRACT: Two enhanced solution treatments (ESTs) were applied to an Al–Cu–Li–Sc alloy. Results showed that the ESTs reduced the amount and size of the soluble phases, and promoted the recrystallisation of the α–Al matrix and the precipitation of the Al2 CuLi precipitate (T1 ), which improved the yield strength, tensile strength and elongation of the alloy. Although the precipitation strengthening of the T1 phase and the strengthening resulting from grain refinement of the α–Al matrix caused by the recrystallisation contributed equally to the strength increment, the EST process led to a greater proportional increase in the strengthening resulting from grain refinement than it did in the precipitation strengthening of the alloy.